POLA RUANG DAN STRATEGI PEMANFAATAN LAHAN BUDIDAYA DI PERAIRAN TELUK KOTANIA, KABUPATEN SERAM BAGIAN BARAT, PROVINSI MALUKU - Koto, Saifuddin; Retraubun, Alex; Sahetapy, Dicky (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2020)
Kotania Bay, West Seram Regency can be clarified as one of the unique bays because it has five smallest islands, which has the important potential coastal ecosystem resources. This bay’s status also has been assigned as a Coastal Conservation Area and Small Islands. These purposes of this research are 1) to know the sub-zone potential cultivation in Kotania Bay, and 2) to analyze and formulate the marine cultivation management strategy in Kotania Bay. The method of data collection used by the researcher are interviews and direct field observations. The data analysis used land suitability index to determine the potential cultivation space (seaweed, sea cucumbers, mangrove crabs and groupers), while the DPSIR is used to produce the marine culture management strategy in Kotania Bay. The potential marine cultivation in Kotania Bay is divided into three sub-zones cultivation with the total area 361,69 ha. The result of the research showed that the suitability of seaweed cultivation land obtained an S1 value of 66% (237.43 ha) and an S2 value of 34% (124.26 ha). The land suitability of the sea cucumber cultivation obtained an S1 value of 94% (340.65 ha) and an S2 value of 6% (21.04 ha). The suitability of cultivated land designated for mangrove crabs, especially the species of Scylla serrata, was obtained very suitable values ​​up to 100%. The cultivation activity for grouper fish obtained an S1 value of 93% (338.06 ha), while for an S2 value of 7% (23.63 ha). There are 11 recommended strategies for the management and development of marine cultivation activities in Kotania Bay. ABSTRAK Teluk Kotania Kabupaten Seram Bagian Barat dapat diklasifikasikan sebagai salah satu teluk yang unik karena memiliki lima pulau sangat kecil, serta memiliki potensi sumberdaya eksoistem pesisir penting. Teluk ini pun telah ditetapkan status sebagai Kawasan Konservasi Pesisir dan Pulau-Pulau Kecil (KKP3K). Penelitian ini bertujuan untuk 1) mengetahui potensi ruang sub-zona budidaya di Teluk Kotania, dan 2) menganalisis dan menformulasikan strategi pengelolaan budidaya laut di Teluk Kotania. Pengambilan data menggunakan metode wawancara dan observasi langsung di lapangan.Analisa data menggunakan indeks kesesuaian lahan untuk mengetahui potensi ruang budidaya (rumput laut, teripang, kepiting bakau dan ikan kerapu), sedangkan DPSIR digunakan untuk menghasilkan strategi pengelolaan budidaya laut di Teluk Kotania. Potensi wilayah budidaya laut di Teluk Kotania dibagi menjadi tiga sub zona budidaya dengan total luas 361,69 ha. Hasil penelitian menunjukkan kesesuaian lahan budidaya rumput laut diperoleh nilai S1 sebesar 66% (237,43 ha) dan nilai S2 sebesar 34% (124,26 ha). Kesesuaian lahan untuk budidaya teripang diperoleh nilai S1 sebesar 94% (340,65 ha) dan nilai S2 sebesar 6% (21,04 ha). Kesesuaian lahan budidaya yang diperuntukkan untuk kepiting bakau terutama spesies Scylla serrata diperoleh nilai sangat sesuai hingga 100%. Kegiatan budidaya untuk ikan kerapu diperoleh nilai S1 sebesar 93% (338,06 ha), sedangkan untuk nilai S2 sebesar 7% (23,63 ha).Terdapat 11 strategi yang direkomendasikan untuk pengelolan serta pengembangan kegiatan budidaya laut di Teluk Kotania. Kata Kunci: Budidaya, indeks kesesuaian, rumput laut, teripang, Teluk Kotania